The Harriet Lane handbook : a manual for pediatric house officers / Keith Kleinman; Lauren McDaniel; Matthew Molloy - Kleinman, Keith
Every three years, The Harriet Lane Handbook is carefully updated by residents, edited by chief residents, and reviewed by expert faculty at The Johns Hopkins Hospital. Easy to use, concise, and complete, this essential manual keeps you current with new guidelines, practice parameters, pharmacology, and more